2015
DOI: 10.1111/nmo.12665
|View full text |Cite
|
Sign up to set email alerts
|

Ehlers Danlos syndrome and gastrointestinal manifestations: a 20‐year experience at Mayo Clinic

Abstract: EDS HM and other subtypes should be considered in patients with chronic functional GI symptoms and abdominal vascular lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
159
5
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 154 publications
(172 citation statements)
references
References 15 publications
7
159
5
1
Order By: Relevance
“…Two studies presented a wrong patient group, 5 reported outcomes related to vascular surgery, and 3 held vascular interventions, and were excluded. The remaining 11 studies met the study eligibility criteria, of which 2 studies held the same 100 patients as a continuum [21,22] , and altogether summed 1,567 patients [4,13,21,29] . In total, 1,312 patients had the diagnosis confirmed by Villefranche criteria, while the remaining patients were retrieved from national EDSs foundations and health clinics with no reported method of diagnosis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two studies presented a wrong patient group, 5 reported outcomes related to vascular surgery, and 3 held vascular interventions, and were excluded. The remaining 11 studies met the study eligibility criteria, of which 2 studies held the same 100 patients as a continuum [21,22] , and altogether summed 1,567 patients [4,13,21,29] . In total, 1,312 patients had the diagnosis confirmed by Villefranche criteria, while the remaining patients were retrieved from national EDSs foundations and health clinics with no reported method of diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…Acute complications were most prevalent in the vascular subtype, both primary manifestations that needed surgical intervention and secondary post-surgical complications. Functional GI symptoms were more prevalent in the hypermobility type and to a lesser extent in the classic type [4] . Reduced life expectancy could not be proven as a general feature of EDSs.…”
Section: Mortality and Gi Manifestationsmentioning
confidence: 95%
See 3 more Smart Citations